EFFACEMENT OF BASAL CISTERNS AS A SINGLE PROGNOSTIC FACTOR IN TRAUMATIC BRAIN INJURY - AHMED , N; REHMAN , L; SHARIF , MM; RAZA , A; KHAN , N (Biological and Clinical Sciences Research Journal, 2024)
Effacement of basal cisterns, a condition characterized by the compression or obliteration of the cerebrospinal fluid (CSF)-filled spaces around the brainstem, is an essential radiological finding in the context of traumatic brain injury (TBI). Objectives: The study's primary purpose is to find the effacement of basal cisterns as a single prognostic factor in traumatic brain injury (TBI). Methods: This prospective observational study was conducted at the Pakistan Institute of Medical Sciences, Islamabad, from June 2023 to May 2024. Data were collected from 250 patients suffering from TBI. For each patient, comprehensive demographic information, including age and gender, was recorded. Additional data included the mechanism of injury, the Glasgow Coma Scale (GCS) score at admission, and the presence of basal cistern effacement as observed on the initial CT scan. Radiological findings, such as midline shift and hematomas, were also documented. Results: The mean age of the patients was 35.6±5.65 years. There were 160 (64%) male and 90 (36%) female patients. Motor vehicle accidents were the most present form of injury 104 (41.6%). The mean GCS score at admission was 7.5 ± 2.1 in the basal cistern group and 12.3 ± 2.8 in the no basal cistern group. The study results revealed a significant association between basal cistern effacement and midline shift, with 61.5% of patients with effacement showing midline shift compared to only 14.8% without effacement (p < 0.01). Conclusion: Basal cistern effacement on initial CT scans is a significant prognostic indicator in traumatic brain injury. Its presence is associated with more severe injury, higher necessity for surgical intervention, and poorer long-term outcomes.